The potential of fermented food from Southeast Asia as biofertiliser - Mohd Zaini, Nurul Solehah; Idris, Hamidah; Yaacob, Jamilah Syafawati; Wan-Mohtar, Wan Abd Al Qadr Imad; Samsudin, Nik Iskandar Putra; Abdul Sukor, Arina Shairah; Lim, Elicia Jitming; Abd Rahim, Muhamad Hafiz (Multidisciplinary Digital Publishing Institute, 2022)
The intensive amount of chemical usage in agricultural practices could contribute to a significant impact on food safety issues and environmental health. Over-usage of chemical fertilisers may alter soil characteristics and contaminate water sources, leading to several human and animal health issues. Recently, there have been efforts to use microbial biofertilisers as a more sustainable and environmentally friendly agricultural practice in the common household of Southeast Asia. Traditionally, this method tends to utilise leftover food materials and readily available bacterial cultures, such as yoghurt drinks, and ferment them under a specific period in either solid or liquid form. So far, most of the testimonial-based feedbacks from local communities have been positive, but only limited information is available in the literature regarding the usage of biofertiliser fermented food (BFF). Previously, raw food waste has been used in the agriculture system to promote plant growth, however, the functional role of fermented food in enhancing plant growth have yet to be discovered. An understanding of the symbiotic relationship between fermented food and plants could be exploited to improve agricultural plant production more sustainably. Fermented food is known to be rich in good microbial flora (especially lactic acid bacteria (LAB)). LAB exist in different sources of fermented food and can act as a plant growth-promoting agent, improving the nutrient availability of food waste and other organic materials. Therefore, in this review, the potential use of seafood-based, plant-based, and animal-based fermented food as biofertiliser, especially from Southeast Asia, will be discussed based on their types and microbial and nutritional contents. The different types of fermented food provide a wide range of microbial flora for the enrichment of proteins, amino acids, vitamins, and minerals content in enhancing plant growth and overall development of the plant. The current advances of biofertiliser and practices of BFF will also be discussed in this review.